The Effect of Pasteurella haemolytica A2 Infection on Phagocytosis efficiency of Caprine Broncho-Alveolar Macrophages - Saad, Mohd Zamri; Rajam, Mera Hidayawati (Blackwell Wissenschafts-Verlag, Berlin, 2001)
An experiment was designed to study the in vivo effect of Pasteurella haemolytica A2 infection on the phagocytosis activity of caprine broncho-alveolar macrophages and the extent of pneumonic lesions. Twelve healthy local Kacang goats, about 7 months of age, were divided into two groups of six. Goats in group 1 were inoculated intratracheally with 4 ml inoculum containing 2.8 × 109 colony-forming units (CFU)/ml of Staphylococcus aureus. Goats in group 2 were inoculated intratracheally with 4 ml of inoculum containing 9.5 × 108 CFU/ml of Pasteurella haemolytica A2 isolated earlier from pneumonic lungs of goat. At intervals of 3 and 7 days post-challenge five goats from each group were killed and the lungs were washed with sterile phosphate-buffered saline. Smears were prepared from the lung washing fluid and the number of macrophages with phagocytic activity was determined. At day 3 post-infection, goats of both groups showed a similar pattern of pneumonic lesion. The lung washing fluid of goats in group 2 was found to contain numerous neutrophils and macrophages. Goats in group 2 showed significantly (P < 0.05) higher extent of lung lesions than group 1. Similarly, the average extent of lung lesions was significantly (P < 0.05) more severe in group 2 at day 7 post-infection. The lung washing fluid contained mostly macrophages. The phagocytic activity following S. aureus infection was more efficient and significantly (P < 0.01) higher compared with infection by P. haemolytica A2. There were weak correlations between the extent of pneumonic lesion and the phagocytic activity. Thus, goats with poor phagocytic activity were likely to develop more extensive lung lesions.